ANALISIS SEMIOTIK NAMA â NAMA SESAJI DALAM PROSESI UPACARA LABUHAN MELASTI DI PANTAI NGOBARAN GUNUNGKIDUL YOGYAKARTA - , HASTI PURNININGRUM ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This paper describes about labuhanmelasti ceremony. This research present semiotical analysisof the offeringâs elements of labuhanmelasti ceremony. The semiotical analysis is used to find the meaning which is contained in the offeringâs elements of the ceremony. This reseach also analysis about the point of the ceremony, the time, and the place of the ritual held, and the procession of labuhanmelasti ceremony. The offeringsin the labuhanmelasti ceremony generally contain of meaning about the prayer for God to be pured from sins and dirts, and to be protected in order to be able to live well, safe, and blessed in everything. Furthermore, hindustans are wished to have traits, like willing to sacrifice, hardwork, sincere, patient, and calmess in living, and to always practice three concepts of the harmony of life.